The Inhibitory Effects of Terminalia catappa L. Extract on the Migration and Invasion of Human Glioblastoma Multiforme Cells - Hsiao-Hang Chung; Ming-Ju Hsieh; Yih-Shou Hsieh; Pei-Ni Chen; Chung-Po Ko; Nuo-Yi Yu; Chiao-Wen Lin; Shun-Fa Yang (Pharmaceuticals, 2021)
Glioblastoma multiforme (GBM) is one of the most aggressive and common types of brain tumor. Due to its high proliferation ability, a high lethality rate has been observed with this malignant glial tumor. Terminalia catappa L. (T. catappa) is currently known to have anti-inflammatory and anti-carcinogenesis effects. However, few studies have examined the mechanisms of the leaf extracts of T. catappa (TCE) on GBM cells. In the current study, we demonstrated that TCE can significantly inhibit the migration and invasion capabilities of GBM cell lines without showing biotoxic effects. Matrix metalloproteinases-2 (MMP-2) activity and protein expression were attenuated by reducing the p38 phosphorylation involved in the mitogen-activated protein kinase (MAPK) pathway. By treating with TCE and/or p38 inhibitor (SB203580), we confirmed that p38 MAPK is involved in the inhibition of cell migration. In conclusion, our results demonstrated that TCE inhibits human GBM cell migration and MMP-2 expression by regulating the p38 pathway. These results reveal that TCE contains potent therapeutic compounds which could be applied for treating GBM brain tumors.